Kajian Literatur tentang Faktor-Faktor yang Memengaruhi Kemampuan Menulis Teks Akademik pada Siswa - Rasmi Ariani Hutagalung; Putri Gabriella Septiani Tarigan; Nurmala Nurmala; Nesya Zahra Salsabila; Nayla Rahmadani; Marsya Angelica Sianipar; Mohammad Khadafi; Ita Khairani (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to examine various factors that can influence students' ability to write academic texts through literature studies. The ability to write academic texts is an important skill that students must have to support success in the learning process, helping students think critically and convey ideas scientifically. The method used is a qualitative research method with a literature review approach by analyzing relevant scientific sources. The results of the study indicate that the ability to write academic texts is influenced by internal and external factors. Internal factors include learning motivation, self-efficacy, reading literacy, and self-regulation skills. Meanwhile, external factors include teacher learning strategies, feedback, the learning environment, writing exercises, and the use of technology in learning. The results also show that academic writing skills are also related to self-confidence, critical thinking skills, and student learning experiences. Therefore, the ability to write academic texts needs to be supported through interactive learning, continuous practice, a supportive learning environment, and the use of technology and literacy culture in education.